Ar–Ar Ages of Hydrothermal Muscovite and Igneous Biotite at the Guposhan–Huashan District, Northeast Guangxi, South China: Implications for Mesozoic W–Sn Mineralization. Issue 2 (April 2015) - Li, Xiaofeng; Xiao, Rong; Feng, Zuohai; Chunxia, Wei; Tang, Yanwen; Bai, Yanping; Zhang, Mingji
Abstract The Guposhan–Huashan district is an important W–Sn–Sb–Zn–(Cu) metallogenic area in South China. It is located in the middle‐west segment of the Nanling Range. Granitoids in the Guposhan–Huashan district possess certain properties of A‐type or I‐type granites. The W–Sn–Sb–Zn mineralization in the district is closely associated with magma emplacement. Two igneous biotite and seven hydrothermal muscovite samples from skarn, veins and greisenization ores were analyzed by Ar–Ar methods. Two igneous biotite samples from fine‐grained quartz monzodiorite and fine‐grained biotite granite show plateau ages of 168.7 ± 1.9 Ma and 165.0 ± 1.1 Ma, respectively. Seven hydrothermal muscovite samples from ores yield plateau ages as two groups: 165 Ma to 160 Ma and 104 Ma to 100 Ma. These data suggest that the emplacement of fine‐grained granitoids in this district is coeval with the main phase magma emplacement, different from previous studies. The W–Sn–Sb–Zn mineralization took place in two stages, i.e. the Middle–Late Jurassic and early Cretaceous. W–Sn mineralization in the Guposhan–Huashan district is closely related to the magmatism, which was strongly influenced by underplating of asthenospheric mantle along trans‐lithospheric deep faults and related fractures.